The Influence of Support System on the Readiness to Motherhood Transition in Padang Independent Midwive Practice - Yulizawati Yulizawati; Henni Fitria; Rafika Oktova (Universitas Andalas, 2022)
This study saw the influence of adult attachment style and support systems on the readiness for the transition to motherhood. It is hoped that there will be an optimization of the preparedness for the motherhood transition for women who give birth for the first time. The long-term goal of this study is to assist mothers in optimizing preparation for the transition period to motherhood and obtaining a healthy pregnancy, minimizing the incidence of complications and morbidity in mothers so that it can contribute to reducing the morbidity rate, maternal mortality rate, and infant mortality rate.The specific target of this study is the achievement of psychological well-being in puerperal mothers, which can be obtained from cooperation with their husbands and social support from their environment.This research activity plan aligns with UNAND's National Research Priorities and Development Master Plan. This research is included in one of PRN's research fields in the focus area of health and drug research. This research is also following the RIP of Andalas University, including the central theme of research, namely health, with the sub-theme of nutrition and health, the sub-topic of development.